The Effect of Wages, Islamic Work Culture and Religiosity on Employee Performance With Job Satisfaction as an Intervening Variable - Nafis Irkhami; Khoerul Soleh; Eko Yuli Sulistiyo (CV. Syntax Corporation Indonesia, 2021)
The Research type which is used in this thesis is quantitative research, with sample counted 99 employees in Company Of Sub-Province of Semarang. accurate variable cover giving of fee, Cultural of activity of Islami, Religiusitas, Performance Officer, Satisfaction of Activity. Method data collecting through kuesioner, data analysis use statistical and descriptive analysis with doubled linear regression. Under the result of research in PT Kamaltex, PT. Ungaran Gist, Sari of Garment, PT Apac of[is Core of indicating that: giving of fee have an effect on positive and significant to officer performance, Cultural of activity of Islami have an effect on positive and signifikan to Performance Officer, Religiusitas have an effect on positive and do not signifikan to Performance Officer, giving of fee have an effect on positive and signifikan to satisfaction of activity, Cultural of activity of Islami have an effect on positive and signifikan to satisfaction of activity, Religiusitas have an effect on positive and signifikan to satisfaction of activity, Satisfaction of activity have an effect on positive and signifikan to officer performance, Satisfaction of activity can memediasi influence of giving of fee to officer performance, Satisfaction of activity can cultural influence memediasi of activity of islami to officer performance, Satisfaction of activity can memediasi influence of religiusitas to officer performance in Company of Sub-Province of Semarang